Negative and Dissolute-Negative Law in Russia - Zakhartsev, Sergey I. (Opción, 2019)
The aim of the study is to investigate the broad spectrum of legal science that was developed by prominent Russian scientists via using the method of dialectical materialism as the main tool for conducting humanitarian studies. As a result, until researchers propose a lot of independent concepts that objectively and fully reveal specific facets of law, a single and common concept cannot be developed. In conclusion, philosophy of law is a science with a philosophical focus, which studies the fundamental problems of ontology, gnoseology, axiology, anthropology, logic, ethics and praxeology of law, legal consciousness, and legal culture.